(untitled) (Research, Society and Development, 2020)
Objective: To report a case of epiploic appendangitis in a patient treated at Clínica Gastromed, emphasizing the clinical, propaedeutic aspects and the treatment adopted. Methodology: This is a retrospective study that will address the case of a patient with epiploic appendangitis, using the patient’s medical record for this purpose. Consultations will be carried out throughout the study period on available and pertinent literature, such as: scientific articles, books, magazines, etc. Results: Male patient, 38 years old, seeks care on May 20, 2019 with complaints of diarrhea, unverified fever and myalgia. Upon examination of the abdomen, pain on superficial and deep palpation in the left iliac fossa, with no pain on sudden decompression, without other changes. Computed tomography of the lower abdomen revealed an ovoid structure with fat density, measuring 1.5 x 0.8 cm, with a hyperdense central point, on the colon’s antimesenteric border suggesting incipient epiploic appendangitis in the left colon. He underwent home monitoring with non-steroidal anti-inflammatory and antispasmodic drugs, with a favorable evolution. Conclusion: In the conditions that were carried out in the present study, we can conclude that epiplomatic appendagitis is an unusual clinical condition that includes in its differential diagnosis several pathologies whose treatment is surgical illustrating the importance of adequate clinical reasoning.